THE INFLUENCE OF FISH MORTALITY ON THE FRESHNESS OF FISH - Suprayitno, Eddy (International Journal of Research -GRANTHAALAYAH, 2018)
Fish is one of the freshly prepared high-protein foodstuffs. Fish protein needs by the body to speed up the digestion process by the similar function as human proteins. Protein has a function as growth, regulatory and former energy. Moreover, fish is the perishable product which is easy to spoil and cause decreasing quality. One of the factors that the caused the decreasing quality of fish is death method. Where fish that the long process of decay death proved more rapid than the fish that quickly intervening died calmly. This research was conducted to investigate the effect of fish mortality on the old phase of deterioration in fish quality. The method was used in this experiment was Completely Randomized Design (CRD) with 6 treatments rooms is left alone, the medulla oblongata stabbed, beaten hard objects, broken spine, given freshwater ice, and smeared with kluwak. The result showed that there was no significant effect (P> 0.05) on the phase of deterioration of fish quality. Which is the longest phase of fish deterioration in the treatment of fish stabbed medulla oblongata with an average value of 2137.8 minutes.